The day the Great War ended, 24 July 1923 the civilianization of war - Winter, Jay 1945- (Oxford University Press, 2022)
On 24th July 1923 the last Treaty ending hostilities in the Great War was signed at Lausanne in Switzerland. Jay Winter tells the story of the peace conference, and its outcome. He shows how peace came before justice, and how the conference and the Treaty set in motion forces leading to the global war that followed in 1939
This edition also issued in print: 2022. - Includes bibliographical references and index
Keywords: Conference on Near Eastern Affairs / (1922-1923 / Lausanne, Switzerland); Conference on Near Eastern Affairs -- 1922-1923 -- Lausanne; Treaty of Lausanne / (1923 July 24); Vertrag von Lausanne -- 1923 Juli 24; Politics and Government / ukslc; Politics & government / thema; Greco-Turkish War, 1921-1922; Population transfers / Greeks / History / 20th century; Population transfers / Turks / History / 20th century; Armenians / History / 20th century; Friedensverhandlung; Erster Weltkrieg; World War, 1914-1918 / Treaties; Turkey / History / Mehmed VI, 1918-1922; Turkey / Foreign relations / Greece; Greece / Foreign relations / Turkey